Enhancing the Security of Internet of Things Devices through Cybersecurity Framework - Macharia, Godfrey M; Mgawe, Bonny; Mvula, Jaha; Sam, Anael E (Journal of Information System and Informatics, 2025)
This study focused on enhancing the protection of IoT devices by assessing the effectiveness of existing cybersecurity frameworks (CSFs), identifying gaps in advanced technology cyber-attack tactics, and developing a comprehensive cybersecurity framework for IoT ecosystems. Technological Acceptance and Zero Trust Security Theories guided the study. A cross-sectional research design and mixed-methods approach was adopted, while semi-structured interviews and Focus Group Discussions provided in-depth qualitative insights. For quantitative data, a questionnaire was used. A total of 93 respondents from HLIs, hospitals, and broadcasting media were selected using purposive and random sampling techniques. Descriptive and inferential statistics were employed to analyze quantitative data. For qualitative data, Atlas.ti 9.0 Desktop was used. The findings revealed cyber vulnerabilities are associated with the spread of imported unsecured IoT devices, user unawareness, and lack of effective cybersecurity frameworks tailored to emerging cyber threats from advanced technologies such as AI, 5G, Edge computing, and Autonomous Systems. In conclusion, a framework was designed to strengthen IoT device security by integrating best practices, policy implementation, and technological safeguards. The study recommends that imported IoT devices should be digitally coded to detect cyber risks and adopt multi-layered ECSF-IoT framework and strengthen end-user cybersecurity education in developing countries such as Tanzania.